PENGARUH PENGGUNAAN MODEL PEMBELAJARAN RADEC (READ,ANSWAR,DISCUSS, EXPLAIN, DAN CREATE) TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS V UPTD SDN 48 BARRU - Rafidah; Andi Adam; Abd Rajab (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The RADEC learning model, which stands for Read, Answer, Discuss, Explain, and Create, is an innovative instructional approach designed to enhance students’ literacy, critical thinking, and creativity in a holistic and integrated manner. This study aims to explore the effectiveness of the RADEC model in the context of Indonesian language learning, particularly in improving students’ abilities to understand texts and express their ideas in a structured and coherent way. Using a pre-experimental method with a One Group Pretest-Posttest design, the research involved 18 fifth-grade students from UPTD SDN 48 Barru. Data collection techniques included observation, interviews, and documentation of classroom learning activities, with a focus on students’ performance in writing explanatory texts. The primary instrument used was a written test, and data were analyzed using both descriptive and inferential statistical methods. The results showed a significant improvement in students’ performance following the implementation of the RADEC model. The average pretest score was 61.11, with a small percentage of students achieving high or very high categories. After the intervention, the average posttest score increased to 88.33, with 83.33% of students falling into the very high category. This substantial improvement indicates that the RADEC model effectively supports students in developing better text comprehension and writing skills, while also encouraging active participation and critical engagement throughout the learning process. In conclusion, the RADEC model proves to be a relevant and impactful strategy for teaching explanatory writing in Indonesian language classes, aligning well with current literacy and competency-based education goals.